Isotopic and magnetic proxies are good indicators of millennial-scale variability of the East Asian monsoon - Fuchs, Louise; Guo, Jingjing; Schefuß, Enno; Sun, Youbin; Guo, Fei; Ziegler, Martin; Peterse, Francien (Springer Nature, 2023)
Past East Asian Monsoon variability has been reconstructed using oxygen isotopes of cave speleothems as well as proxy indicators from Chinese loess sequences. However, where the speleothem record is dominated by precession cycles, loess magnetic susceptibility primarily shows a glacial-interglacial pattern. Here we generate a ~ 130,000 years high resolution record of plant wax hydrogen isotopes from a loess section on the western Chinese Loess Plateau that can directly be compared with both speleothem oxygen isotopes and with magnetic susceptibility from the same section. We find that variations in our plant wax hydrogen isotope record follow the precessional pattern of the speleothem record as opposed to the glacial-interglacial changes in magnetic susceptibility. We propose that hydrogen isotopes mainly record precipitation during the growing season, whereas magnetic susceptibility represents an annual climate signal, including precipitation and temperature. Our findings imply that summer vs annual climate variability is driven by distinct orbital forcings.
Keywords: SDG 13 - Climate Action